The Influence of Laboratory Analyst Performance, Examination Equipment and Work Environment on Patient Satisfaction in Hospital X Through Waiting Time Efficiency Laboratory Examination Results - Kamelia Ghalib; Rudianto Rudianto; Jones Zenas Rante; Ratnawati Prayogi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study examines the influence of laboratory analyst performance, examination equipment, and work environment on patient satisfaction at Hospital X through the efficiency of laboratory test result waiting times. This research employs a quantitative method. The sample consists of the entire population, using a saturated sampling/census technique, which includes 15 laboratory staff and 15 patients who visited the laboratory at Hospital X, selected through a non-probability sampling technique. Data collection was conducted using a questionnaire, and data analysis was carried out using the Smart PLS 4 method. The results are as follows: 1) Laboratory analyst performance, examination equipment, and work environment do not influence the efficiency of laboratory test result waiting times. 2) Laboratory analyst performance, examination equipment, and work environment do not influence patient satisfaction at Hospital X. 3) The efficiency of laboratory test result waiting times influences patient satisfaction at Hospital X. This study demonstrates that patient satisfaction at Hospital X is affected by the efficiency of laboratory test result waiting times.